Self-Regulation Behaviors of Hypertension and Related Factors Among Hypertensive Patients - Majid Barati; Davod Darabi; Abbas Moghimbeigi; Ali Afsar (Fasa University of Medical Sciences, 2011)
Background & Objectives: Hypertension is the most important cause of all cardiovascular diseases, stroke, heart attack, renal disease, which is usually incurable. Management of the disease requires a certain degree of self-regulation. The aim of this study was to investigate the self-regulation behaviors of hypertension and related factors among hypertensive patients. Material & Methods: This Cross sectional study was carried out on 328 hypertensive patients referring to rural health centers of Bahar District in Hamadan Province, who were selected in two stages. First, the rural health centers were selected through cluster sampling in Bahar District and then the patients were selected by simple sampling method in the rural health centers. Data was gathered using a questionnaire whose reliability and validity were approved by the experts (α=0.83). Data was analyzed by SPSS13 software program using coefficient correlation, T-Test, One-way Anova. Results: The average score of self-regulation scale was 7.26 that indicated 7.9% of hypertensive patients have a good status in self-regulation behaviors. Significant differences in average score of self-regulation behaviors related to, age, gender, education level, marital status, and blood pressure were seen in last follow up (P <0.05). Conclusion: The findings show that, health systems and authorities in addition to qualitative studies should pay more attention to the benefits, barriers and potential threats in the auto regulation of blood pressure behavior. Also more active and powerful health education units, medical refresh courses, and regular targeted training classes should be held for the patients.